ANALYSIS OF ACCOUNTABILITY, TRANSPARENCY, AND FINANCIAL INNOVATION IN IMPROVING THE QUALITY OF BUREAU AND LIVING LAB SERVICES - Vannessa Efendi; Kholilul Kholik (RADJA PUBLIKA, 2024)
This study examines how financial governance accountability, transparency, and innovation affects service quality in bureaus and living laboratories. Combining qualitative and quantitative methods, we find that robust financial accountability drives efficient resource allocation, transparency builds stakeholder trust, and financial innovation optimizes service quality. This research sheds light on the intricate relationship between financial governance and service quality, offering actionable insights for organizational enhancement.